Personalized Recommender System for Calculus using Content-Based Filtering Approach - Latiffah Adam, Noor; Alif Zulkafli, Muhammad; Cik Soh, Shaharuddin; Ashikin Mohamad Kamal, Nor; Abu Bakar, Nordin (International Journal of Engineering and Technology, 2018)
In this millennial age, Internet is becoming essential to human kind. Along with the growth of Internet users, information is also becoming huge and starting to cause difficulties to find the relevant contents. Thus, the recommender system was introduced. It helps the user to suggest the items based on the userâ€™s preferences. This system could help the students as Calculus is one of the tough subjects feared by most students. Credits given to the technology as many sources on the web can provide tutorials, working examples and solutions on the subjects. However, there are too many of them. Students had to make a few selections, which one can fulfil their needs of specific calculus topics. The personalized recommender system developed was a content-based filtering recommender system with its own scraping engine to collect the sources from the Internet which focuses on the basic Calculus topics. The system and engine were constructed by using Flask framework together with its relevant libraries.Â